2022
DOI: 10.1111/jce.15480
|View full text |Cite
|
Sign up to set email alerts
|

Cardioneuroablation for vasovagal syncope and atrioventricular block: A step‐by‐step guide

Abstract: Catheter-based cardioneuroablation is increasingly being utilized to improve outcomes in patients with vasovagal syncope and atrioventricular block due to vagal hyperactivity.There is now increasing convergence among enthusiasts on its various aspects, including patient selection, technical steps, and procedural end-points. This pragmatic review aims to take the reader through a step-by-step approach to cardioneuroablation: we begin with a brief overview of the anatomy of intrinsic cardiac autonomic nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Anatomical map of the LA was acquired using CARTO 3 (Biosense Webster, Diamond Bar, CA) or NavX (Abbott, USA) and fused with CT images. Areas where GPs are usually located 8 were searched for fragmented EGM (fEGMs) (i.e., showing 4 deflections) but ablated based on anatomical landmarks independently from the presence of fragmentation. As from June 2022, epicardial fat pads near the area of anticipated GPs with attenuation -190 to -30 Hounsfield Units (HU) were segmented, exported using ADAS3D software (Galgo Inc.), and integrated in electro-anatomical maps for real-time guidance of GP ablation (Figure 1).…”
Section: Cardioneuroablationmentioning
confidence: 99%
See 2 more Smart Citations
“…Anatomical map of the LA was acquired using CARTO 3 (Biosense Webster, Diamond Bar, CA) or NavX (Abbott, USA) and fused with CT images. Areas where GPs are usually located 8 were searched for fragmented EGM (fEGMs) (i.e., showing 4 deflections) but ablated based on anatomical landmarks independently from the presence of fragmentation. As from June 2022, epicardial fat pads near the area of anticipated GPs with attenuation -190 to -30 Hounsfield Units (HU) were segmented, exported using ADAS3D software (Galgo Inc.), and integrated in electro-anatomical maps for real-time guidance of GP ablation (Figure 1).…”
Section: Cardioneuroablationmentioning
confidence: 99%
“…The ablation end-point for each GP was defined as abolition of RF-induced vagal response for LSGP, MTGP and LIGP increase in basal HR 25% for the SPSGP, RIGP and Ao-SVC GPs, and shortening of at least 25% of AH interval for the IPSGP 8,16 .…”
Section: Cardioneuroablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in recent years it has been demonstrated that cardiac denervation of parasympathetic ganglia can be highly effective in reducing cardioinhibitory reflex syncope, a technique known as cardioneuroablation[ 43 ]. Tilt test might play a crucial role in detecting suitable patients for this promising procedure[ 44 ].…”
Section: Diagnostic Approach and Testmentioning
confidence: 99%
“…“Abandonment” of high-frequency stimulation has not been prevalent, less so at the time of this procedure early in 2021, and labs that exclude high-frequency stimulation generally do so in favor of an electrogram-only approach, rather than replacing it with extracardiac vagal stimulation, as implied. 1 , 2 , 3 We are interested in the potential of extracardiac vagal stimulation to optimize denervation assessment; however, its incorporation in mainstream CNA workflows has been, as Drs Pachon cite, quite limited.…”
mentioning
confidence: 99%